Bringing the outside in: Connecting students' out-of-school knowledge and experience through translanguaging in Hong Kong English Medium Instruction mathematics classes. (December 2020) - Tai, Kevin W.H.; Wei, Li
Abstract: The present study contributes to a well-established line of applied linguistics research in educational contexts on how teachers can make connections between their students' out-of-school knowledge and experiences and what they learn in the classroom by examining a hitherto under-explored context, namely English-medium-instruction (EMI) mathematics classes in Hong Kong (HK). Adopting a translanguaging perspective, the study examines how fluid and dynamic meaning-making practices afford opportunities for teachers to bring the outside into the EMI classroom in order to support the students' learning of new academic knowledge. The data for the present paper is based on a linguistic ethnography project in a HK secondary school where EMI is practised. Multimodal Conversation Analysis is carried out on the classroom interactional data, triangulated with the video-stimulated-recall-interview data analysed using Interpretative Phenomenological Analysis. The findings demonstrate how the teacher constructs a translanguaging space by integrating the students' everyday life experience in an institutional learning space. It is argued that translanguaging thus helps to transform the EMI classroom into a lived experience, which in turn enhances content learning. The theoretical and pedagogical implications for EMI in other contexts are explored.